“It’s all in their head!” Rhetoric in the fibromyalgia wars - Gascón, José Ángel (Rivista Italiana di Filosofia del Linguaggio)
While most research on argumentation in medicine studies doctor-patient communication, this article focuses on a case of argumentation among medical professionals. Eight editorials from a well-known specialized journal, constituting a single discussion about the diagnosis of fibromyalgia (FM), are studied from a rhetorical perspective. Several rhetorical strategies are identified and commented on, illustrating how, at least outside research reports, scientists do not merely argue in a neutral way about empirical facts. In particular, I will focus on the frames used by the arguers, the appeals to common values, and the ethotic arguments that are used.